2012
DOI: 10.1007/s00035-012-0103-2
|View full text |Cite
|
Sign up to set email alerts
|

High genetic differentiation in populations of the rare alpine plant species Campanula thyrsoides on a small mountain

Abstract: Changes in climate and traditional land use have contributed to a loss and fragmentation of suitable habitats for many alpine plant species. Despite the importance of these changes, our knowledge of the consequences for gene flow and genetic diversity is still poor, especially in rare taxa and at fine spatial scales. Here, we investigated the genetic diversity in a rare alpine plant on a small and highly structured mountain in the Swiss Alps. Using microsatellite markers and Bayesian cluster analyses, we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 78 publications
(84 reference statements)
1
15
0
Order By: Relevance
“…Higher diversity in highland populations, as in our study in C. flava , was found in some studies, e.g. for Cystopteris fragilis (Pteridophyta) using isozymes (Gämperle and Schneller 2002), for Primula farinosa (Primulaceae) using RAPD analysis (Reisch et al 2005) and for Campanula thyrsoides (Campanulaceae) (Frei et al 2012), and was suggested to be due to higher mutation rates due to elevated radiation (Li et al 1997). However, others reported higher diversity of lowland populations, as we found for C. viridula (e.g.…”
Section: Discussionsupporting
confidence: 76%
“…Higher diversity in highland populations, as in our study in C. flava , was found in some studies, e.g. for Cystopteris fragilis (Pteridophyta) using isozymes (Gämperle and Schneller 2002), for Primula farinosa (Primulaceae) using RAPD analysis (Reisch et al 2005) and for Campanula thyrsoides (Campanulaceae) (Frei et al 2012), and was suggested to be due to higher mutation rates due to elevated radiation (Li et al 1997). However, others reported higher diversity of lowland populations, as we found for C. viridula (e.g.…”
Section: Discussionsupporting
confidence: 76%
“…Their remarkable population differentiation in various traits indicates that even at small spatial scales, populations may be substantially differentiated, either as the result of genetic drift or as an adaptation to their local environments. However, such differentiation is only possible when gene flow is restricted, as has recently been found for populations from this particular area [40], [41] (but see [42]). …”
Section: Discussionmentioning
confidence: 72%
“…Due to the current, strong isolation of C. thyrsoides populations in a heterogeneous environment and limited seed and insect-mediated pollen dispersal [40], [41], gene flow between populations since postglacial recolonisation is probably weak though not absent [12], [42]. This may have prevented homogenisation of phenotypic differentiation across populations from the phylogeographic regions, although considerable genetic introgression may be present between populations from the CSA and CAA regions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Are genetic bottlenecks unusual for alpine species? A number of studies (Paun et al 2008;Muster et al 2009;Frei et al 2011;Shama et al 2011) have recently shown that demographic history plays a larger role in shaping current patterns of genetic differentiation in alpine species and that the influence of large and ⁄ or recent population size changes may not be uncommon.…”
Section: Patterns Of Genetic Variation In Alpine Specie: Demographic mentioning
confidence: 99%